Effect of adding locally probiotic and Cupric Sulphate to Laying Hens Diets on the Performance , Egg Yolk Cholesterol and Blood biochemical Parameters - Mousa, B.H.; AL-Rawi, A.J. (Journal of Kerbala for Agricultural Sciences, 2015)
The present experiment aimed to study the effect of diets supplementation with local probiotic (IRAQI PROBIOTIC ™), and cupric sulphate (CuSo4) on performance of shaver laying hens. A locally prepared probiotic were used each one gram of this probiotic contain Lactobacilli , Lactobacillus acidophilus, Bacillus subtilus and Saccharomyces cerevisiae yeast. A total of 112, 42 week old, Shaver laying hens were divided into 7 treatments with 4 replicates per treatment (4 laying hens per replicate). Laying hens in T1 were fed a basal diet used as control. Laying hens in T2, T3 and T4 were fed diets supplemented with 5 ,10 and 15gm/kg ration of local probiotic respectively, Laying hens in T5,T6 and T7 were fed diets supplemented with 100,200 and 300ppm of cupric sulphate respectively. The experiment was conducted at the poultry farm belong to Animal Resources, College of Agriculture, University of AL- Anbar . During the experimental periods hens performance traits included egg production, egg weights, egg mass, feed consumption, and feed conversion ratio were recorded, At the end of the experimental periods blood serum and egg yolk samples were collected for cholesterol analysis and biochemical which including glucose, protein, albumin, globulin, triglycerides, high density lipoprotein (HDL), low density lipoprotein (LDL), very low density lipoprotein (VLDL), Liver weights, GOT and GPT enzymes. A significant increase (p<0.05) of record the laying hens supplemented with local probiotic T2 (adding local probiotic 5 gm/kg) , T3 (adding local probiotic 10 gm/kg) ,T4 (adding local probiotic 15 gm/kg) in egg production and egg mass as compare with other treatments. In general the study revealed that there were a significant improvement (P<0.05) in feed conversion ratio of T2(adding local probiotic 5 gm/kg) ,T3 (adding local probiotic 10 gm/kg) ,T4 (adding local probiotic 15gm/kg) ration compared with T1(control). Serum cholesterol concentration, triglycerides, low density lipoprotein (LDL) and very low density lipoprotein (VLDL) were decreased markedly by both local probiotic and cupric sulphate supplementation, while high density lipoprotein (HDL) increased in both local probiotic and cupric sulphate treatments. There were no differences (p>0.05) regarding in feed intake, total glucose ,total protein, total albumin, total globulin ,liver weight, GOT and GPT enzymes